(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
Background: Amavata is the most common form of inflammatory arthopathy seen in India. Among adult population below the age of 50 years this is the most common form of arthritis. For the present study, on Amavata as shaman therapy, Khanda Shunthi and Prasarni Avleha the Ushnaveeryadravya medicaments were chosen. Aims & Objective: The present research work aimed at to evaluate efficacy and establish safe use of Khanda Shunthi and Prasarni Aavaleha in Amavata. Materials & Methods: 40 subjects of Amavata fulfilling the inclusion criteria were selected from OPD and IPD of Desh Bhagat Ayurvedic Hospital, Mandi Gobindgarh, Punjab and randomly divided into two groups, group A and B, comprising each of 20 patients. Group-A subjects received Khanda Shunthi for 60 days, Group-B subjects received Prasarni Avaleha for 60 days. Assessments were done on 0th and 60th day of treatment. Results and Conclusions: In both the groups, highly significant results were observed in all the cardinal parameters with P value for fever and Hb are greater than 0.05 hence there is no significant difference in effect of Group A and Group B on fever and Hb. P values for all other symptoms are less than 0.05 hence we conclude that there is significant difference in effect of group A and group B on pain, swelling, stiffness, fever, ESR, walking time and grip strength. On comparison group A treatment is more effective than group B for all assessment criteria.